JOB SECURITY ANALYSIS OF EMPLOYE INTENTION TO LEAVE THROUGH EMPLOYE ENGAGEMENT - Firdaus Firdaus (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Objective research This is For know influence direct or not direct job security towards employee intention to leave and influence employee engagement towards employee intention to leave as well the influence of job security on employee intention to leave via employee engagement. Method study use method descriptive quantitative population target study all over working employees special do production at 42 MSMEs in Sasirangan, South Kalimantan with number of 796 employees. Based on calculation obtained amount minimum sample of 266. Collection sample done with proportional cluster random sampling technique . Research results show that Job security has an influence significant on Employee Engagement of Sasirangan MSME employees in South Kalimantan. Job security matters significant on Employee Intention to Leave employees of UMKM Sasirangan in South Kalimantan. Employee Engagement has an influence significant on Employee Intention to Leave employees of UMKM Sasirangan in South Kalimantan. Employee Engagement is capable mediating Job security for Employee Intention to Leave employees of Sasirangan MSMEs in South Kalimantan. Keywords: job security, employee intention, employee engagement